Isolation of Rhizopus oryzae From Rotten Fruit and Its Potency For Lactic Acid Production in Glucose Medium with and without Addition of Calcium Carbonate - Titik Kurniawati; Retno Indrati; Sardjono Sardjono (agriTECH, 2014)
Studies on lactic acid production by filamentous fungi Rhizopus oryzae have been explored in the world. Unfortunately, these studies are still limited in Indonesia, particularly studies in lactic acid production by indigenous strain R. oryzae. Four strains obtained from rotten avocado and guava were potential in producing lactic acid (AT1, JT1, AT2, and AT3). Rhizopusoryzae AT3 was used for lactic acid production using 100 g/l glucose medium with and without addition of 7.5 g/l calcium carbonate (CaCO3) at initial fermentation. Addition of CaCO3 increased lactic acid concentration of 59.30%, the concentrations were 11.61 g/l and 18.495 g/l in glucose medium and glucose medium with CaCO3 addition, respectively. Glucose+CaCO3 medium also showed higher productivity, reached continuously from 1 day (0.059 g/l/h) until 5 days fermentation (0.154 g/l/h), whereas highest productivity in glucose medium was reached at 1 day fermentation (0.124 g/l/h) and continued to decrease until 5 days fermentation (0.065 g/l/h).